Hygroscopically induced residual stresses in composite laminates - Thinh, Tran Ich; Khoa, Ngo Nhu (Vietnam Journal of Mechanics, 2001)
In this paper the exact moisture concentration function m(z, t) is used to compute the hygroscopic residual stresses in laminated composites. The governing equations were established by using a full higher-order displacement theory. Hygroscopically induced residual stresses in thick graphite-epoxy composite laminates: Cross-ply [0/90] 8 based on this approach were compared with those obtained by assumption: the moisture concentration m is a constant in all plies through the laminates thickness